Effect of concentration of rapeseed oil to Tribotechnical contact options - Мнацаканов, Р.Г.; Лізанець, В.І. (Problems of Tribology, 2014)
The paper discusses the influence of concentration of rapeseed oil in mineral oil I-20A on the formation of adsorption layers and their lubricating action at local contact that allows to establish patterns of wear of friction pairs. The relationships of lubricating layer in the contact. The influence of boundary layers on a change of microhardness of surface layers of operating time.